Starving for Justice: Bangladeshi garment workers in a 'Post-Rana Plaza' world - Siddiqi, Dina Mahnaz (© 2015 International Labor and Working-Class History, Inc., 2016)
This review was published in the International Labor and Working-Class History [© 2015 International Labor and Working-Class History, Inc.] and the definite version is available at: http://doi.org/10.1017/S0147547915000101 The article website is at: https://www.cambridge.org/core/journals/international-labor-and-working-class-history/issue/F0FEB691268D3C4C7D2970D4CAF6DDD1